Reproducible metacarpal joint space width measurements using 3D analysis of images acquired with high-resolution peripheral quantitative computed tomography - Barnabe, Cheryl; Buie, Helen; Kan, Michelle; Szabo, Eva; Barr, Susan G.; Martin, Liam; Boyd, Steven K. (Medical engineering & physics, 2013)
Joint space narrowing is an important feature of progressive joint damage and functional impairment in rheumatoid arthritis (RA). Methods to provide a continuous measurement of joint space width have not been adopted in research or clinical settings. High-resolution peripheral quantitative computed tomography (HR-pQCT) (Scanco Medical AG, Brüttisellen, Switzerland) accurately and reproducibly images bone microstructure at a nominal isotropic voxel dimension of 82μm. Given the ability of HR-pQCT to detect bone margins with high precision, we developed methodology to measure a three-dimensional (3D) metacarpophalangeal (MCP) joint space width and tested the reproducibility of the scan protocol with hand repositioning. Consecutive HR-pQCT scans of the 2nd and 3rd MCP joints of ten subjects with early RA (70% female, mean age 45 years), with repositioning between scans, were obtained. The periosteal edges of the metacarpal head and proximal phalanx base were detected using the μCT Evaluation Program V6.0 (Scanco Medical AG). Using the method of ‘fitting maximal spheres’, the joint space width and distribution of joint space thickness was estimated. The mean minimum joint space width of the 2nd MCP was 1.82mm (SD 0.20) and of the 3rd MCP 1.84mm (SD 0.23). Reproducibility with repositioning was reliable, with overlapping filtered histograms and a root square mean coefficient of variance of 4.8%. We provide reproducible methodology for evaluating the joint space width of the MCP joints. When combined with the assessment of erosions and periarticular bone density, HR-pQCT may be the ideal technology to assess disease activity and progression in RA.